Diseño e implementación de unidades de conversión de energía eléctrica para uso en redes de generación a partir de fuentes no convencionales - Trujillo Rodríguez, Cesar Leonardo; Peña Suesca, Rafael Antonio; Guacaneme Moreno, Javier Antonio (Revista Científica, 2006)
In many places of the world there are zones where it is really complex to transport the electrical energy. In these cases, a solution is to provide itseif with own systems of generation in which the advantage of non-conventional power sources presented in these zones can be considered. An alternative is the design of a system that transforms and stores energy in a bank of batteries and, from this one, to convert it to values standard AC (e.g. 120V/60Hz). These conversions must be highly efficient, since generally it is energy available during certain periods, in many cases little and expensive one. In this paper is analyzed the convertion stage from a DC bus which provides a storage media of the energy that is collected through some type of source. They are also analyzed the operation principies, sizing of the components and characteristics of design for the implementation of DC/AC electronic units of conversion of low power able to handle active power and reactive power in both directions (from the batteries towards the network and vice versa) and with possibility of interconnection to others generation systems. Moreover, a practical analysis of the performance of the electronic unit is described.